ZELENI MARKETING KAO DETERMINANTA KONKURENTSKE PREDNOSTI NA b2b TRŽIŠTIMA - Jovičić, Dragoljub; Ilić, Dragan; Raletić Jotanović, Saša (International Journal of Economic Practice and Policy, 2024)
Given the fact that in the professional literature on marketing, and especially in the segment of green (environmental) marketing, much more research is done and written about B2C markets, this paper is an attempt to explore procurement motives and behavior of business customers during the complex purchasing process, on the example of several important thermotechnical devices, on the B2B market in Vojvodina. The aim of the research is to collect relevant data from business customers through direct interviews regarding the impact of some environmental performance on the procurement of gas boilers, heat pumps and air conditioners, in order to obtain quality and reliable information based on the process, that is, conducted descriptive statistical analysis, which will enable a better understanding of this complex issue. To collect qualitative data the method of unstructured deep interview was used. The obtained results confirmed the research hypotheses and indicated the necessity of applying green marketing in modern business conditions. It is indisputable that soon only organizations focused on green marketing and green marketing channels, that is to say those which are focused on creating own optimal relationship between their production, distribution and/or sales process, and environmental protection, will be able to gain a competitive advantage in dynamic business markets and achieve maximum satisfaction of environmentally demanding customers, and thus, in fact, at the same time give their full contribution to the sustainable development of the entire community.